MAINSTREAM ACCOUNTING AND ITS PARADIGM: A CRITICAL ANALYSIS - Imam Wahyudi (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 1999)
This paper discusses the methodology dominantly used in accounting research, namely, mainstream accounting research methodology. This methodology which relies on the methodology of natural sciences and is called hypothetico-deductive approach assumes that human beings are passive objects and has no power to create social realities. As a result, accounting tends to be seen as an objective information separated from its social environment.This belief has created many disadvantages to the development of accounting practices and accounting research itself. Accounting research tends to be separated from accounting practices. Consequently, a lot of research findings cannot be applied in accounting practice. Thus, accountingresearch and accounting theorizing may not produce a real answer to the accounting problems.